MAQASID AL-SYARI’AH DALAM PANDANGAN JASSER AUDA - Prihantoro, Syukur (At-Tafkir, 2017)
The fundamental problem in Islamic law (Maqasid al-Syari?ah) is how the goal of Islamic law can be useful for justice and bring benefit for all levels of society. However, the effort to bring justice in law is a dinamic and long time process. Through system approach, Jasser Auda tries develops a new frame of mind for the development of Islamic law in this era. There are six concepts of Auda system approach; Cognition, Wholeness, Opennes, Interrelated-Hierarchy, Multidimensionality and Purposefulness. This article discuss about those six concepts and the implementation in Isamic law.